Hubungan Asupan Vitamin D, Asupan Lemak, dan Paparan Sinar Matahari dengan Tekanan Darah Pada Remaja di SMPN 21 Tangerang Selatan - Novita Harumsari (2023)
Hypertension is a global health problem that can occur in adolescents. Based on Riskesdas 2018, the prevalence of national hypertension is 34.1%, Banten Province is 29.4%, and South Tangerang City is 27.5%. This study aims to determine the association between vitamin D intake, fat intake, and sun exposure in adolescents at SMPN 21 Tangerang Selatan. This study used a cross-sectional design with a sample of 102 respondents taken using stratified random sampling technique. Data was collected by measuring blood pressure, Sun Exposure Questionnaire (SEQ), and the Semi Quantitative Food Frequency Questionnaire (SQ-FFQ). Association analysis was performed using the chi-square test and fisher's exact test showing that there was an association between sun exposure (p = 0.046; OR = 7.902) with blood pressure and there were no association between vitamin D intake (p = 0.760) and fat intake (p = 1.000) with blood pressure in adolescents at SMPN 21 South Tangerang.